Enhanced Selectivity and Stability of Finned Ferrierite Catalysts in Butene Isomerization. (29th December 2021) - Dai, Heng; Lee, Choongsze; Liu, Wen; Yang, Taimin; Claret, Jakob; Zou, Xiaodong; Dauenhauer, Paul J.; Li, Xiujie; Rimer, Jeffrey D.
Abstract: Designing zeolite catalysts with improved mass transport properties is crucial for restrictive networks of either one‐ or two‐dimensional pore topologies. Here, we demonstrate the synthesis of finned ferrierite (FER), a commercial zeolite with two‐dimensional pores, where protrusions on crystal surfaces behave as pseudo nanoparticles. Catalytic tests of 1‐butene isomerization reveal a 3‐fold enhancement of catalyst lifetime and an increase of 12 % selectivity to isobutene for finned samples compared to corresponding seeds. Electron tomography was used to confirm the identical crystallographic registry of fins and seeds. Time‐resolved titration of Brønsted acid sites confirmed the improved mass transport properties of finned ferrierite compared to conventional analogues. These findings highlight the advantages of introducing fins through facile and tunable post‐synthesis modification to impart material properties that are otherwise unattainable by conventional synthesis methods. Abstract : The synthesis of finned ferrierite produces a zeolite with reduced mass transport limitations, thereby enhancing its catalyst lifetime and increasing its selectivity to isobutene in tests of 1‐butene isomerization. These findings highlight the advantages of introducing fins through facile and tunable post‐synthesis modification to impart material properties that are otherwise unattainable by conventional synthesis methods.